Tendering and biosimilars: what role for value-added services? - Steven Simoens; Raymond Cheung (Journal of Market Access & Health Policy)
Background: Access to biologic medicines (including biosimilars) across Europe is largely governed by a process of tendering conducted by health authorities. Over-reliance on treatment costs in awarding tenders has the potential to hinder competition and undermine the long-term sustainability of biosimilars. Objective: To assess the extent and impact of consideration of ‘value-added services’ (VAS) in tendering for biosimilars, we conducted a narrative review of published literature. Results: Findings from survey-based publications indicated that tendering practices for biosimilars are widely used, with cost being the main determinant of success and little detail being available on other criteria where these apply. Criteria (of therapeutic and technical interest) beyond price were included in one tendering specification for infliximab (originator and biosimilars), while a separate tender for the same product included VAS in the form of therapeutic drug monitoring, measurement of antibodies and calprotectin. Conclusions: Published evidence concerning inclusion of VAS in tendering for biosimilars is lacking. Development and implementation of standardized criteria and methods of assessment for tenders may avoid manufacturers facing segmented markets, encourage competition and the longer-term sustainability of biosimilars, and realize the healthcare system and patient benefits these treatments can bring.